Variation in Formation of Superficial Palmar Arches with Clinical Implications - Joshi, Sheetal Bhimprasad (JCDR Research and Publications (P) Limited, 2014)
Background: Knowledge of the variations in the arterial supply of hand has reached a point of practical importance with the advent of microvascular surgery for revascularization, replantation and composite tissue transfers. Arterial supply of hand is derived from two anastomotic arches, formed between two main arteries of forearm i.e. radial, ulnar and their branches, in the palm. Objective: The superficial palmar arch shows variation in formation at the radial side. In the present study we have recorded its data which would help in its clinical and surgical implications. Material and Methods: In the present study we have studied the formation of superficial palmar arches and their variations in 100 cadaveric hands at Dr. D . Y. Patil Medical College, Pune and B.J. Government Medical College, Pune, India. Result and Conclusion: According to Adachi’s classification the most predominant pattern obseved was of Ulnar type arch (66%). According to Coleman and Anson classification 82% showed complete (Group I) superficial palmar arches and a very low incidence (18%) of incomplete arches (Group II). This suggests that collateral circulation is present in majority of cases. This would result in least number of complications considering radial artery harvesting for coronary bypass. Sub-classification of arches according to Coleman and Anson 1961 indicates that the predominant type in the present study was of Group I (Type B) which is formed entirely by Ulnar Artery (56%). Median artery and ulnar artery forming an incomplete superficial arch under Group II (Type C) having an incidence of 4% was recorded. Thus in such cases radial artery harvesting for coronary artery bypass may prove to be less fatal. This study is an effort to provide data about the formation of superficial palmar arches which has been a centre of attraction for most of the surgical procedures and injuries of the hand.